2011
DOI: 10.1158/1535-7163.mct-11-0008
|View full text |Cite
|
Sign up to set email alerts
|

Time-Course Imaging of Therapeutic Functional Tumor Vascular Normalization by Antiangiogenic Agents

Abstract: We describe here new technology that enables noninvasive imaging of therapeutic functional normalization of tumor blood vessels by antiangiogenic agents. Noninvasive variable-magnification in vivofluorescence imaging as well as fluorescence tomography was used to visualize functional vessel normalization. Changes in the same vessel before and after drug treatment were imaged with high resolution in real time. Differences in vascular responses to the mTOR inhibitor rapamycin and to an anti-VEGF antibody were fu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 31 publications
2
33
0
Order By: Relevance
“…Nevertheless there is strong evidence that transient application of antiangiogenic agents can "normalize" the abnormal tumor microvessels (7,8). This prudent application of antiangiogenic therapy might result in effective uptake of drugs and oxygen in the tumor-enhancing cytotoxic therapeutic outcome in cancer therapy (4,9).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless there is strong evidence that transient application of antiangiogenic agents can "normalize" the abnormal tumor microvessels (7,8). This prudent application of antiangiogenic therapy might result in effective uptake of drugs and oxygen in the tumor-enhancing cytotoxic therapeutic outcome in cancer therapy (4,9).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have demonstrated evidence of vessel normalization and increased therapeutic uptake. [22][23][24] There are also a series of studies that demonstrate the opposite effect of decreased uptake of therapeutic following anti-VEGF administration. 25 The notion that there is a therapeutic window based on dose and time likely explains these discrepant findings.…”
Section: Discussionmentioning
confidence: 99%
“…BBB compromise in EAE is well characterized [29], and AngioSense, a validated NIR vascular imaging agent [30,31], offers an opportunity for in vivo imaging of vascular leak into the CNS. In addition, as proteases play a central role in cancer and inflammatory disease processes, we anticipated that protease-activatable NIR imaging agents [32,33] could serve as a sensitive means for detecting neuroinflammation in EAE and changes with therapeutic intervention.…”
Section: Discussionmentioning
confidence: 99%